Study of Humoral Immune Response In Children Infected With Visceral Leishmaniasis (Baghdad Science Journal, 2025)
40 blood sample were taken from children infected with kala-azar at age less than ten years, who were admitted to El-Eskan child hospital, and central health laboratory in Baghdad. At the same time 15 sample collected from healthy child for comparing. During research estimated immunoglobulins level ( IgG, IgM, IgA) and (IFAT) IFAT test recorded a higher indicate antibodies level witch was synergistic with infected severity, the stander level of antibodies arrange between 1/16, 1/32 and 1/64 that means it graduate from the lowest one 1/16 into the highest one 1/64 within groups. During infectious the IgG ,IgM level recorded the higher level (2012.9 mg/dl) and (154.3 mg/dl) compared to the control group (874.3 mg/dl), (91.4 mg/dl) while there no significant differences in IgA level between patients group( 143.8 mg/dl ) And healthy control group (116.2 mg/dl) .